Polymers of phenyldiacetylenes - functional thermostable additions to industrial resins - Misin, Vjacheslav; Glagolev, Nikolay; Misin, Michael (Publishing House of Lviv Polytechnic National University, 2010)
High thermal and thermooxidation stability of homo and copolymers of diphenyldiacetylene and p-diethynylbenzene was established. The amount of coke residue, obtained from commercial epoxy-resins, is essentially increased upon their modification with added polymers.Additions of polydiethynylbenzene to commercial olygoetheracrylates improved their thermooxidation stability. Встановлено високу термічну і термоокиснюючу стабільність гомо- і кополімерів дифенілдіацетилену і п-діетинілбензену. Показано, що при додаванні полімерів кількість коксового залишку, одержаного з промислових епоксиднихс мол, суттєво зростає. Додавання полідіетинілбензену суттєво підвищує термоокиснюючу стабільність промисловихол ігоестеракрилатів.
Фенілдіацетиленові полімери - функційні термостабільні додатки до промислових смол
Keywords: polyconjugated polymers; thermostability; thermooxidation resistance; resins; oligoetheracrylate; compound; поліспряжені полімери; термостабільність; стійкість до термоокиснення; смоли; олігоестеракрилат; компонент